A method for preparing a fully biodegradable antistatic film bag
Through the combination of modified starch, nano-concave and convex rod soil/polylactic acid composite and PBAT, combined with multi-stage pickling and silane coupling treatment of nano-concave and convex rod soil, the problem of lack of antistatic properties of membrane bags in the fully degraded material is solved, and higher antistatic effects and full degradation performance are achieved.
Patent Information
- Application Number
- CN202310233625.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-03-13
AI Technical Summary
The existing fully degraded material film bags lack anti-static properties, which leads to static electricity easily in dry areas or long-term friction, resulting in packaging difficulties or adsorption of products to be packaged.
Modified starch, nano-concave and concave rod soil/polylactic acid composite and PBAT are used as the main base materials, and plant fibers are treated by multi-stage pickling, combined with silane coupling treatment of nano-concave rod soil to enhance the porosity and hydrophilicity of the material, thereby enhancing the antistatic effect.
It effectively improves the anti-static effect of the film bag, enhances the convenience of use and packaging safety, and ensures the full degradation performance of the material.
Smart Images

Figure CN116144059B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fully degradable material processing, and in particular to a method for preparing a fully biodegradable antistatic film bag. Background Art
[0002] Plastic film bags are a commonly used packaging material in life processing and production. They are widely used in various fields due to their light weight and convenience. Generally, traditional plastic film bags are mostly made of PE materials. Although they are easy to use, they will cause certain environmental pollution due to their non-degradable characteristics. Therefore, we are now starting to develop degradable materials to replace traditional plastic bag materials.
[0003] Existing fully degradable materials include polylactic acid, PBAT and other materials. When degradable materials are used to prepare plastic film bags, these film bags can be degraded after use to reduce pollution. Since the "Plastic Ban" in 2008, the demand for degradable plastics has increased year by year, so film bags made of degradable materials have gradually replaced traditional film bags as packaging materials.
[0004] As packaging materials, not only environmental issues should be considered, but also the safety and convenience of practical applications should be considered. For the packaging of electronic devices, since they are very sensitive to static electricity, ordinary biodegradable film bags do not have antistatic properties and cannot achieve the purpose of safe packaging. At the same time, in dry areas or under long-term friction, the film bags are prone to static electricity, resulting in adsorption and sticking between the packaging film bags, or adsorption of the corresponding products to be packaged, thereby causing packaging difficulties. Most existing methods are to spray a layer of antistatic film on the surface of the film bag, which can effectively solve the static electricity problem, but the processing cost is high, and the overall processing procedure is also relatively cumbersome. In addition, the antistatic film layer on the surface of the film bag may also fall off due to friction during long-term use, reducing its antistatic effect. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a fully biodegradable antistatic film bag, which effectively improves the antistatic effect while effectively ensuring the full degradation performance of the film bag, thereby improving the scope of use and convenience of use of the film bag.
[0006] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:
[0007] A method for preparing a fully biodegradable antistatic film bag, the method comprising the following steps:
[0008] (1) Preparation of modified starch: corn starch is mixed with clean water and heated for gelatinization, then the pressure is increased and high-speed stirring is performed for mechanical modification, and finally freeze-dried and ground to obtain modified starch for use;
[0009] (2) Pretreatment of nano-attapulgite: After calcining the nano-attapulgite, mix the silane coupling agent and disperse it in clean water by ultrasonic, then centrifuge to obtain a precipitate and dry it to obtain pretreated nano-attapulgite;
[0010] (3) Preparation of nano-attapulgite / polylactic acid composite: The pretreated nano-attapulgite and propiolactone were mixed, and then a tetrahydrofuran solution of stannous octoate was added and stirred, and then vacuumed and polymerized for 26-30 hours to obtain a nano-attapulgite / polylactic acid composite;
[0011] (4) Preparation of modified plant fiber: The plant fiber is acid-washed and soaked in acid solutions of pH 4, pH 5.5, and pH 6.5 in sequence, then rinsed with clean water, taken out, dried, and ground to obtain modified plant fiber powder for later use;
[0012] (5) Mixing: Add the modified starch, nano-attapulgite / polylactic acid composite, modified plant fiber powder, PBAT, thermoplastic starch, antistatic agent, coupling agent, opening agent, chain extender, and monoglyceride into a mixer to mix and obtain a mixture for later use;
[0013] (6) Blending: placing the above-mentioned mixed material in a twin-screw extruder, mixing and then extruding and granulating to obtain antistatic degradation particles for use;
[0014] (7) Film bag preparation: The above-mentioned antistatic degradable particles are placed in a high-pressure film blowing machine for film blowing to obtain a film roll, and then the film roll is placed in a bag making machine for bag making to obtain a fully biodegradable antistatic film bag.
[0015] Preferably, in step (1), the temperature for heating and gelatinization of corn starch is 75° C., the gelatinization time is 15-20 min, the pressure of the boosted high-speed stirring is 10-12 MPa, the stirring speed is 1000-1200 r / min, and the stirring time is 20-25 min.
[0016] Preferably, in the step (2), the nano-attapulgite is calcined at a temperature of 300-320° C. for a calcination time of 20-30 min, and the frequency of ultrasonic dispersion is 20 KHz for a dispersion time of 20-30 min.
[0017] Preferably, in the step (3), the mass ratio of nano-attapulgite to propiolactone is 3:97.
[0018] Preferably, the pickling and soaking method in step (4) is to soak the plant fiber in an acid solution with a pH of 4 for 20 minutes, then adjust the acid solution to pH 5.5 and continue soaking for 10 minutes, and finally adjust the acid solution to pH 6.5 and continue soaking for 10 minutes, and the modified plant fiber powder is passed through a 100-mesh sieve.
[0019] Preferably, the mass ratio of the components in the step (5) is modified starch: nano-attapulgite / polylactic acid composite: modified plant fiber powder: PBAT: thermoplastic starch: antistatic agent: coupling agent: opening agent: chain extender: monoglyceride = 10-12: 20-25: 2-3: 55-60: 4-6: 0.5: 0.3: 0.3: 0.3: 0.7-0.9, and the mixing speed is 1000r / min, and the mixing time is 20min.
[0020] Preferably, in the step (5), the antistatic agent is a mixture of antistatic agent FA14 and antistatic agent FE2 in a mass ratio of 1:1; the coupling agent is a silane coupling agent; the opening agent is a mixture of oleic acid amide and silicon dioxide in a mass ratio of 3:1; and the chain extender is chain extender ADR-43685.
[0021] Preferably, the zone temperatures of the twin-screw extruder in step (6) are: zone 1 temperature 170°C, zone 2 temperature 175°C, zone 3 temperature 180°C, zone 4 temperature 180°C, zone 5 temperature 175°C, the die extrusion temperature is 170°C, and the mixing time in each zone is 30-40 minutes. The temperature of the film blowing in step (7) is 145°C-155°C.
[0022] The present invention provides a method for preparing a fully biodegradable antistatic film bag, which has the following advantages over the prior art:
[0023] (1) The present invention adopts modified starch, nano-attapulgite / polylactic acid composite and PBAT as the main base materials, which can effectively ensure the full degradation performance of the material. At the same time, by compounding the nano-attapulgite / polylactic acid composite with modified starch and modified plant fiber, the porosity and hydrophilicity of the overall material are improved, and the antistatic effect of the material is further improved.
[0024] (2) The present invention treats the plant fiber by multi-stage acid washing during preparation, which can effectively improve the porosity of the plant fiber and ensure that there are pores of different sizes in the plant fiber, which is convenient for the subsequent formation of a combined skeleton with the nano-attapulgite / polylactic acid composite material, and at the same time facilitates the uniform dispersion of the antistatic agent, thereby improving the overall antistatic uniformity;
[0025] (3) The nano-attapulgite of the present invention is surface treated with a silane coupling agent before being compounded with polylactic acid. The silane coupling agent is hydrolyzed in water to produce silanols. The silanol bonds are mutually condensed into oligomers. Some silanol bonds condense with exposed hydroxyl groups on the surface of the attapulgite to form hydrogen bonds. The hydrogen bonds are dehydrated and condensed to convert into covalent bonds. The mechanism of cationic surfactant modification is to replace inorganic cations in attapulgite with long carbon chain organic cations to expand the interlayer spacing. At the same time, some surfactants are adsorbed on the surface of the attapulgite, thereby enhancing the binding ability with organic matter, facilitating subsequent compounding, and further improving the antistatic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the antistatic test of the film bag in the experimental group 2 of the present invention;
[0027] Figure 2 Schematic diagram of antistatic testing of film bags in experimental group 6 of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Embodiment 1:
[0030] Preparation of raw materials:
[0031] 1. Preparation of modified starch: Mix corn starch with clean water and heat to 75°C, gelatinize for 18 minutes, then increase the pressure to 12 MPa, adjust the speed to 1200 r / min, continue stirring for 20 minutes for mechanical modification, then take out the freeze-dried powder, grind it and pass it through a 100-mesh sieve to obtain modified starch.
[0032] 2. Preparation of nano-attapulgite / polylactic acid composite (OAT / PLA):
[0033] (1) Pretreatment of nano-attapulgite: The nano-attapulgite was calcined at 320° C. for 20 min, then mixed with vinyl triethoxysilane in 3 times the volume of clean water and ultrasonically dispersed at a frequency of 20 kHz for 25 min, then centrifuged to obtain a precipitate, which was then dried to obtain pretreated nano-attapulgite;
[0034] (2) Preparation of composite materials: The above-mentioned pretreated nano-attapulgite and propiolactone were mixed in a mass ratio of 3:97 and placed in a sealed tube container, 0.05 mol / L of stannous octoate tetrahydrofuran solution was added and magnetically stirred, the container was evacuated under the protection of a nitrogen atmosphere and then sealed, the sealed container was prepolymerized in an oil bath environment at 150°C for 2h, and then polymerized at 150°C for 24h, and then the material was collected to obtain an OAT / PLA composite material.
[0035] 3. Preparation of modified plant fiber: Soak ramie fiber in pH 4 acid solution at room temperature for 20 minutes, then adjust the acid solution to pH 5.5 and continue soaking for 10 minutes, and finally adjust the acid solution to pH 6.5 and continue soaking for 10 minutes. After soaking, rinse with clean water, dry and grind through a 100-mesh sieve to obtain modified plant fiber powder.
[0036] 4. Opening agent: oleamide and silicon dioxide are mixed in a mass ratio of 3:1.
[0037] 5. Antistatic agent: The antistatic agent FA14 and FE2 of Clariant of Germany are mixed in a mass ratio of 1:1.
[0038] 6. Chain extender: select chain extender ADR-43685;
[0039] 7. Vinyltrimethoxysilane is selected as coupling agent.
[0040] Embodiment 2:
[0041] Preparation of fully biodegradable antistatic film bags:
[0042] (1) Add the raw materials according to the mass ratio in Table 1 below into a mixer (select some of the raw materials in Example 1 above), mix at a speed of 1000 r / min for 20 min, and obtain a mixed material for use;
[0043] (2) placing the above mixed material in a twin-screw extruder, setting the temperature of zone 1 to 170° C., the temperature of zone 2 to 175° C., the temperature of zone 3 to 180° C., the temperature of zone 4 to 180° C., the temperature of zone 5 to 175° C., and the head temperature to 170° C., mixing in each temperature zone for 30 min, and finally granulating, using a cold conveyor belt to cool the particles to obtain antistatic degradation particles for use;
[0044] (3) Film bag preparation: The above-mentioned antistatic degradable particles are placed in a high-pressure film blowing machine, the temperature is adjusted to 150°C for film blowing, and then the blown film roll is placed in a bag making machine for bag making to obtain a fully biodegradable antistatic film bag.
[0045] Table 1
[0046]
[0047] As can be seen from Table 1 above, PLA was used in experimental group 4 to replace the OAT / PLA composite in experimental group 2; compared with experimental group 2, thermoplastic starch was used in experimental group 5 to replace modified starch; compared with experimental group 2, thermoplastic starch was used in experimental group 6 to replace modified starch, PLA was used to replace OAT / PLA composite, and ramie fiber powder was used to replace modified plant fiber powder.
[0048] Detection:
[0049] 1. The antistatic degradable particles obtained in each experimental group in the above Example 2 were tested for their full degradation performance:
[0050] The biodegradation rate was tested using GB / T 19277.1-2011 standard: the specific test conditions were that the dry weight ratio of the compost and the test material in each compost container was about 6:1; the test system was aerated with de-CO2 air so that the oxygen concentration discharged from each compost container was not less than 6%, and the test was conducted at 58°C ± 2°C and in the dark; the carbon dioxide release was determined by titration, and the biodegradation rate at different times was tested. The results are shown in Table 2 below:
[0051] Table 2
[0052]
[0053]
[0054] As shown in Table 2 above, although the modified starch, OAT / PLA composites and modified plant fiber powder used in experimental groups 1, 2 and 3 have a low degradation rate in the early stage, they have a fast degradation rate in the later stage and a high final degradation efficiency. The main reason is that the modified starch and OAT / PLA composites have a tight overall structure and are not easy to degrade in the initial stage of degradation. However, after a period of degradation, the entire structure disintegrates during the degradation process due to the presence of multiple skeleton structures, thereby improving the subsequent degradation efficiency.
[0055] 2. After the fully biodegradable antistatic film bags obtained in each experimental group in the above Example 2 were stored naked for 12 hours, they were tested using an electrostatic resistance instrument MODEL-100. The specific results are shown in Table 3 below:
[0056] Table 3
[0057] Group Experimental Group 1 Experimental Group 2 Experimental Group 3 Experimental Group 4 Experimental Group 5 Experimental Group 6 Resistance (Ω) <![CDATA[10 10 ]]> <![CDATA[10 10 ]]> <![CDATA[10 10 ]]> <![CDATA[10 9 ]]> <![CDATA[10 9 ]]> <![CDATA[10 8 ]]>
[0058] It can be seen from the above table that experimental groups 1-3 have better antistatic effects than experimental groups 4-6.
[0059] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0060] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a fully biodegradable antistatic film bag, characterized in that: The preparation method of the fully biodegradable antistatic film bag comprises the following steps: (1) Preparation of modified starch: corn starch is mixed with water and heated for gelatinization, then the pressure is increased and high-speed stirring is performed for mechanical modification, and finally freeze-dried and ground to obtain modified starch for use; (2) Pretreatment of nano-attapulgite: After calcining the nano-attapulgite, mix the silane coupling agent in clean water and disperse by ultrasonication, then centrifuge to obtain a precipitate and dry it to obtain pretreated nano-attapulgite; (3) Preparation of nano-attapulgite / polylactic acid composite: The pretreated nano-attapulgite and propiolactone were mixed, and then a tetrahydrofuran solution of stannous octoate was added and stirred, and then vacuumed and polymerized for 26-30 hours to obtain a nano-attapulgite / polylactic acid composite, wherein the mass ratio of the nano-attapulgite to propiolactone was 3:97; (4) Preparation of modified plant fiber: The plant fiber is acid-washed and soaked in acid solutions of pH 4, pH 5.5, and pH 6.5 in sequence, then rinsed with clean water, taken out, dried, and ground to obtain modified plant fiber powder for later use; (5) Mixing: Add the modified starch, nano-attapulgite / polylactic acid composite, modified plant fiber powder, PBAT, thermoplastic starch, antistatic agent, coupling agent, antiblocking agent, chain extender, and monoglyceride into a mixer for mixing to obtain a mixture for use, and the mass ratio of each component is modified starch: nano-attapulgite / polylactic acid composite: modified plant fiber powder: PBAT: thermoplastic starch: antistatic agent: coupling agent: antiblocking agent: chain extender: monoglyceride = 10-12: 20-25: 2-3: 55-60: 4-6: 0.5: 0.3: 0.3: 0.3: 0.7-0.9; (6) Blending: placing the above-mentioned mixed materials in a twin-screw extruder, mixing and then extruding into granules to obtain antistatic degradation granules for use; (7) Film bag preparation: The above-mentioned antistatic degradable particles are placed in a high-pressure film blowing machine for film blowing to obtain a film roll, and then the film roll is placed in a bag making machine for bag making to obtain a fully biodegradable antistatic film bag.
2. The method for preparing a fully biodegradable antistatic film bag according to claim 1, characterized in that: In the step (1), the temperature for heating and gelatinizing the corn starch is 75° C., the gelatinization time is 15-20 min, the pressure for high-speed stirring is 10-12 MPa, the stirring speed is 1000-1200 r / min, and the stirring time is 20-25 min.
3. The method for preparing a fully biodegradable antistatic film bag according to claim 1, characterized in that: In the step (2), the nano-attapulgite is calcined at a temperature of 300-320° C. for a calcination time of 20-30 min, and the frequency of ultrasonic dispersion is 20 KHz for a dispersion time of 20-30 min.
4. The method for preparing a fully biodegradable antistatic film bag according to claim 1, characterized in that: The pickling and soaking method in step (4) is to soak the plant fiber in an acid solution with a pH of 4 for 20 minutes, then adjust the acid solution to a pH of 5.5 and continue soaking for 10 minutes, and finally adjust the acid solution to a pH of 6.5 and continue soaking for 10 minutes, and the modified plant fiber powder is passed through a 100-mesh sieve.
5. The method for preparing a fully biodegradable antistatic film bag according to claim 1, characterized in that: In the step (5), the mixing speed is 1000 r / min and the mixing time is 20 min.
6. The method for preparing a fully biodegradable antistatic film bag according to claim 1, characterized in that: In the step (5), the antistatic agent is obtained by mixing antistatic agent FA14 and antistatic agent FE2 in a mass ratio of 1:1; the coupling agent is a silane coupling agent; the opening agent is obtained by mixing oleic acid amide and silicon dioxide in a mass ratio of 3:1; and the chain extender is chain extender ADR-43685.
7. The method for preparing a fully biodegradable antistatic film bag according to claim 1, characterized in that: In the step (6), the zone temperatures of the twin-screw extruder are: zone 1 temperature 170ºC, zone 2 temperature 175ºC, zone 3 temperature 180ºC, zone 4 temperature 180ºC, zone 5 temperature 175ºC, the die extrusion temperature is 170ºC, and the mixing time in each zone is 30-40min.
8. The method for preparing a fully biodegradable antistatic film bag according to claim 1, characterized in that: The temperature of the film blowing in step (7) is 145°C-155°C.
Citation Information
Patent Citations
Attapulgite / polylactic acid nano composite material and preparation method thereof
CN106479143A
Full-biodegradable mulching film and preparation method thereof
CN115304894A